2003
DOI: 10.1056/nejmoa031178
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of CD3δ Deficiency on Maturation of α/β and γ/δ T-Cell Lineages in Severe Combined Immunodeficiency

Abstract: he t-cell-receptor complex consists of the a and b or g and d variant chains, paired as mutually exclusive heterodimers in association with the invariant chains CD3 g , d , e , and z . T cells with a and b chains are referred to as a / b T cells, and those with g and d chains are called g / d T cells. During development, the CD3 protein complex plays an important part in the transition of thymocytes from CD4¡CD8¡ double-negative immature precursors to a CD4+CD8+ double-positive stage and finally to the mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
131
1
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(146 citation statements)
references
References 30 publications
(20 reference statements)
4
131
1
10
Order By: Relevance
“…As noted previously, CD3␦ Ϫ/Ϫ mice are blocked in development at the DP thymocyte stage but preserve normal pre-TCR function (45,46). In contrast, CD3␦-deficient humans have an early developmental block at the level of the pre-TCR (47,48). CD3␥ Ϫ/Ϫ mice, in contrast, are blocked at the DN stage as noted above (27), while human CD3␥ deficiency leads to mild thymic alterations with development of both DP and SP thymocytes (49).…”
Section: Discussionmentioning
confidence: 72%
“…As noted previously, CD3␦ Ϫ/Ϫ mice are blocked in development at the DP thymocyte stage but preserve normal pre-TCR function (45,46). In contrast, CD3␦-deficient humans have an early developmental block at the level of the pre-TCR (47,48). CD3␥ Ϫ/Ϫ mice, in contrast, are blocked at the DN stage as noted above (27), while human CD3␥ deficiency leads to mild thymic alterations with development of both DP and SP thymocytes (49).…”
Section: Discussionmentioning
confidence: 72%
“…Although the same authors showed that isolated ␣␤ and ␦⑀ dimers do not normally assemble into ␣␤(␦⑀) 2 complexes in vitro, intrathymic selection mechanisms may expand, in vivo, the otherwise rare T cell precursors that manage to assemble a viable surface TCR⅐CD3 complex with such stoichiometry. In vivo observations further support this contention, because human CD3␥-deficient individuals showed significant T cell development with only mild lymphopenia and immunodeficiency, whereas CD3␦-deficient patients had no T cells and very severe clinical abnormalities (35).…”
Section: Fig 6 Characterization Of the Rw2-8c8 Antibody A Purifiedmentioning
confidence: 79%
“…Microarray experiments may also provide insight into biological or pathogenetic mechanisms [8][9][10][11]. However, to our knowledge no microarray analyses in CVID have been reported.…”
Section: Introductionmentioning
confidence: 99%